(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
Affect belongs to a pre-verbal domain of intensity. It is recognisable as ’emotion’ or ’feeling’, a subjective content that is a socio-linguistic adaptation in the service of convention, even more so with current widespread attempts to measure and regulate affect. Although normally neglected because crudely perceived as unstructured and chaotic, affect is crucial in the process of transformation.